POTENSI LIMBAH PADI SEBAGAI SUMBER ENERGI ALTERNATIF DI PROVINSI SULAWESI TENGGARA - Budiman Sudia; Sudarsono Sudarsono; Nanang Endriatno; Samhuddin Samhuddin; Al Ichlas Imran; Aminur Aminur; Prinob Aksar (Jurusan Teknik Mesin, Universitas Halu Oleo, 2020)
Potentials of Rice Waste as Alternative Energy Sources in Southeast Sulawesi Province. The purpose of this study is to analyze the energy potential of rice processing waste (rice straw and rice husk) in the province of Southeast Sulawesi. Grain production data used the results of the Central Statistics Agency of Southeast Sulawesi publication as well as the Central Statistics Agency of the Regency / municipality of Southeast Sulawesi. To determine the pattern of utilization of rice processing waste at the farm level, the research team conducted a survey in several locations that produce rice in Southeast Sulawesi Province. The data used for analysis were grain production in 2010 – 2018. Based on the grain production, rice straw and rice husk production were calculated, then the energy potential of the two rice processing wastes can be determined. The results of the analysis show that the average production of rice straw was 823, 665 tons; rice husk was 119,289 tons, estimated energy potential of rice straw = 9,600GJ / year and rice husk = 1,700 GJ /year